Nutritional Status and Micro Nutrient Deficiencies Among adolescents: A Pilot Study from Northern India (P18-101-19). (13th June 2019) - Kankaria, Ankita; Duggal, Mona; Gupta, Parul Chawla; Jamir, Limalemla; Kumar, Akash; Singh, Neha; Saxena, Pragati; Zohmangaihi, Deepy; Grover, Sandeep; Das, Reena; Ram, Jagat
Abstract: Objectives: To study the nutritional status and prevalence of RBC folate, Serum folate and vitamin D deficiency among adolescents. Methods: A cross sectional pilot study was carried out among 96 adolescents visiting outpatient department for refraction at tertiary care hospital in North India. Anthropometric data was obtained for height in centimetres and weight in kilograms. A pretested questionnaire was used to capture quantitative data. Venous blood samples were collected where red blood cell (RBC), serum folate and serum Vitamin D concentrations were measured. Anaemia was defined as normal, mild, moderate and severe as Hb > 12gm/dl, 11–11.9 gm/dl, 8–10.9 gm/dl and < 8 gm/dl respectively. Serum folate deficiency was defined as serum folate < 7 nmol/l, and RBC folate deficiency and insufficiency were defined as RBC folate < 305 nmol/l and & < 748 nmol/l, respectively. Vitamin D deficiency, insufficiency and sufficiency was defined as 25(OH)D < 20 ng/ml, 20–29 ng/ml and ≥ 30 ng/ml respectively. Descriptive statistics and inferential statistics were used. Results: Almost 46% of adolescents were malnourished (10.4% were underweight, 35.4% were overweight or obese) and mean BMI was 19.7 kg/meter2 however it did not differ significantly across gender. As compared to boys more girls were vegetarian by diet. The mean concentrations for Hb, serum folate and RBC folate were 12.7 (95% CI: 12.4, 13.0) gm/dl, 15.1 (95% CI 12.5, 17.7) nmol/L and 492.9 (95% CI 431.9, 553.9) nmol/L, respectively. Mean concentration for Hb was significantly different across gender (p – 0.0). Around 17% of adolescents were anaemic, 60% were deficient for serum folate and 79% were deficient for RBC folate. Mean serum vitamin D levels were 18 ng/dl (95% CI: 17.0, 22.3) no significant difference found across gender. A total of 62.5% were deficient and 28% were insufficient for vitamin D (ng/ml). Around 50% of the adolescents lack adequate sleep (<8 hours) and increase vitamin D levels were associated with increase sleep duration (r-0.02, p-0.02). Conclusions: The nutritional status of adolescents in this study is poor and reflects a need to conduct a community-based study which can help in planning strategies to improve nutritional status during critical period of adolescence Funding Sources: nil. Supporting Tables, Images and/or Graphs: